Relationship between income and repeat criminal victimization in Brazil - Marcelo Justus; Tulio Kahn; Henrique Kawamura (EconomiA, 2015)
This study analyzes the effect of income on repeat criminal victimization in Brazil using data from the 2009 National Household Sample Survey and its special supplement on victimization and access to justice. Two count-data models were estimated for four types of crime: theft, robbery, attempted theft/robbery, and physical assault. A positive nonlinear effect of income on repeat victimization for the three types of property crimes and a negative nonlinear effect of income on physical assault were observed. – – Analisamos o efeito da renda na vitimizaç\~ao criminal repetida utilizando dados da PNAD 2009 e do seu suplemento especial sobre vitimizaç\~ao e acesso à justiça no Brasil. Foram estimados dois modelos de dados de contagem para quatro tipos de crime: furto, roubo, tentativa de furto/roubo e agress\~ao física. Concluímos que há uma relaç\~ao n\~ao-linear positiva entre renda e vitimizaç\~ao repetida para crimes contra a propriedade, e uma relaç\~ao n\~ao-linear negativa para agress\~ao física.
Keywords: K42; C25; 330; Repeat victimization; Crime; Violence; Income